2019
DOI: 10.3389/fpls.2019.00496
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhiza in Highly Fertilized Maize Cultures Alleviates Short-Term Drought Effects but Does Not Improve Fodder Yield and Quality

Abstract: Under fertilization levels specific to intensive farming, the impact of compensation of soil nutritional value by arbuscular mycorrhiza (AM) might be limited. Therefore, the question arises whether modern crop varieties, selected for high NPK assimilation rate, are able to gain symbiotic benefits under other challenging field conditions, such as drought. Accordingly, in this study we aimed to evaluate the contribution of Rhizophagus irregularis to the drought response of a stay-green cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 58 publications
1
24
0
2
Order By: Relevance
“…Under water deficit conditions, plants reduce transpiration rate by closing stomata to maintain the normal swelling pressure of cells. Therefore, the relative high G s in the +AMF treatment under salt stress may be related to the increased water absorption under salt stress by +AMF (Hodge et al 2009;Polcyn et al 2019). In addition to the limitation of stomatal factors, the photosynthetic capacity of plants is often reduced by non-stomatal factors under severe stress, such as decreased activity of the dark reaction-related enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under water deficit conditions, plants reduce transpiration rate by closing stomata to maintain the normal swelling pressure of cells. Therefore, the relative high G s in the +AMF treatment under salt stress may be related to the increased water absorption under salt stress by +AMF (Hodge et al 2009;Polcyn et al 2019). In addition to the limitation of stomatal factors, the photosynthetic capacity of plants is often reduced by non-stomatal factors under severe stress, such as decreased activity of the dark reaction-related enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) acquire energy by infecting the roots of host plants (Campos-Soriano and Segundo 2011 ), and rely on the host plants to complete their life cycle (Borde et al 2017). However, AMF also promotes the growth of host plants by promoting the uptake of nutrients (Karagiannidis et al 2002;Evelin et al 2009) and water (Hodge et al 2009;Polcyn et al 2019) by the host plants, which are mutually beneficial to the plant and fungi. Many experiments have reported that AMF can enhance plant stress resistance (Porcel et al 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…There are some other examples of beneficial fungi such as Glomus spp. and other arbuscular mycorrhizal fungi (AMF) [58][59][60][61][62][63] or the endophyte P. indica [64] that also have wide host ranges and show beneficial effects under different conditions. It has been shown that P. indica promotes vegetative growth and early flowering, improves seed germination, and increases yield in multiple plant species [13].…”
Section: Discussionmentioning
confidence: 99%
“…A great many studies in the literature test the effect of arbuscular mycorrhizal fungi or water deficit in MAP, and a lesser amount examine the interaction of both according to Jayne and Quigley (2014). However, over the past five years, more papers have been published on the interaction of both factors on crops and MAP (Sun et al, 2017;Huang et al, 2017;Gheisari et al, 2017;Polcyn et al, 2019). A major goal of most studies examining water and mycorrhizal colonization is to improve the overall performance of plants with agricultural and horticultural importance, such as basil (Copetta et al, 2006;Hazzoumi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%